Trends of High-Impact Studies in Pharmacology and Pharmacy: A Cross-Sectional Study - Chen, Lingmin; Yang, Yi; Fan, Jin; Zhang, Yonggang; Li, Nian (Frontiers in Pharmacology, 2021)
Objective: To investigate the trends of high-impact studies in pharmacology and pharmacy research and to provide evidence for future research in the field of pharmacology and pharmacy. Methods: A cross-sectional study was performed to understand the current status of high-impact studies (top 1%) in pharmacology and pharmacy research via InCites tool based on Web of Science Core Collection; a visualization software VOS Viewer was also used. The outcomes included development trends, countries, subject areas, research institutes, collaborative networks, and subject terms. Results: We found 4273 high-impact (top 1%) studies between 2011 and 2020 in the field of pharmacology and pharmacy. The number of studies increased from 366 in 2011 to 510 in 2020. These studies were mainly distributed in the following Web of Science subject categories: pharmacology pharmacy (n = 4188), neurosciences (n = 397), chemistry multidisciplinary (n = 359), chemistry medicinal (n = 314), microbiology (n = 301), and biotechnology applied microbiology (n = 280). These studies were cited in 646,855 studies from more than 100 Web of Science subject categories, and studies in pharmacology pharmacy accounted for the largest share of these citations. The top three countries that contributed the highest numbers of the studies were the USA, UK, and China. The top three institutions that contributed the highest number of studies were the USA—University of California System, National Institutes of Health (NIH), and Harvard University. The top research collaborative circle was from universities in the USA. The top international collaborative circle was from universities from the USA, UK, Australia, and China. The subject-term analysis indicated that cancer was still the top disease, NF-κB was the top signaling pathway, and drug-delivery and nanoparticles were the top methods. Conclusion: The high-impact studies in pharmacology and pharmacy research have grown over time. USA, UK, and China are the top countries that contributed to the high-impact studies. Cancer is still the leading challenge for treatment. It calls for more international collaboration in pharmacology and pharmacy research, which will help discover novel drugs.